Access to Enantiomerically Pure P‐Stereogenic Primary Aminophosphine Sulfides under Reductive Conditions. Issue 72 (28th October 2022) - Huber, Tanja; Espinosa‐Jalapa, Noel Angel; Bauer, Jonathan O.
Abstract: Stereochemically pure phosphines with phosphorus‐heteroatom bonds and P ‐centered chirality are a promising class of functional building blocks for the design of chiral ligands and organocatalysts. A route to enantiomerically pure primary aminophosphine sulfides was opened through stereospecific reductive C−N bond cleavage of phosphorus(V) precursors by lithium in liquid ammonia. The chemoselectivity of the reaction as a function of reaction time, substrate pattern, and chiral auxiliary was investigated. In the presence of exclusively aliphatic groups bound to the phosphorus atom, all competing reductive side reactions are totally prevented. The absolute configurations of all P ‐stereogenic compounds were determined by single‐crystal X‐ray diffraction analysis. Their use as synthetic building blocks was demonstrated. The lithium salt of ( R )‐BINOL‐dithiophosphoric acid proved to be a useful stereochemical probe to determine the enantiomeric purity. Insights into the coordination mode of the lithium‐based chiral complex formed in solution was provided by NMR spectroscopy and DFT calculations. Abstract : A route to enantiomerically pure P ‐stereogenic primary aminophosphine sulfides by reductive C−N bond cleavage with lithium in liquid ammonia is presented. Undesirable side reactions during the cleavage can be suppressed by using aliphatic substitution patterns. Quantum chemical and spectroscopic insights into a complex of a chiral primary aminophosphine sulfide and the lithium salt of ( R )‐BINOL‐PSSH in solution was provided.